COVID-19 and violent actors in the global south: An inter- and cross-regional comparison - André Bank; Yannick Deepen; Julia Grauvogel; Sabine Kurtenbach (German Institute of Global and Area Studies (GIGA), 2022)
This Working Paper examines the effects of the COVID-19 pandemic on state and non-state violent actors in the Global South. We provide an ACLED-based interregional mapping of trends in Latin America and the Caribbean, the Middle East and North Africa, and subSaharan Africa. Cross-regional case comparisons shed further light on the similarities and differences of countries characterised by long-term armed conflict (Colombia, Iraq, Nigeria) or having transitioned from authoritarianism but facing inequality and political exclusion (Chile, Tunisia, South Africa). We identify a temporal variation: Initially, state armed actors' new responsibilities to implement COVID-19-related control measures led to an increase in violence against civilians, but over time there was a decrease. We also find that COVID-19 had an early demobilising effect vis-à-vis protest and mob violence, a consequence of lockdowns and mobility restrictions. Yet, protest has quickly returned to pre-pandemic levels in many countries, underlining continued - sometimes aggravated -grievances. Moreover, different violent actors' responses to the pandemic were decisively shaped by their respective conflict histories.
Keywords: 300; COVID-19; violence; Global South; Latin America and Caribbean; Middle East and North Africa; sub-Saharan Africa